2x-49=17

Simple and best practice solution for 2x-49=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-49=17 equation:


Simplifying
2x + -49 = 17

Reorder the terms:
-49 + 2x = 17

Solving
-49 + 2x = 17

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '49' to each side of the equation.
-49 + 49 + 2x = 17 + 49

Combine like terms: -49 + 49 = 0
0 + 2x = 17 + 49
2x = 17 + 49

Combine like terms: 17 + 49 = 66
2x = 66

Divide each side by '2'.
x = 33

Simplifying
x = 33

See similar equations:

| 2c^2=-3c | | 4(T-5)+2=-9+c+5 | | 2x+6=-38 | | x^2+x^2-14x-49=169 | | 6x+7(-2x-17)=-175 | | 13x^2+39x=0 | | 3(j-6)=j+10 | | (2x+8)(2x+7)= | | 3q^2-6q=0 | | 20+5x=55 | | cox(2x)-9=0 | | 2x+5=11x-4 | | 3x-4-(2x+3)=0 | | 100x=0.81 | | 7500.00+155.00=92440 | | C=240+8k | | f(x)=tan^2(x)-3 | | f(x)=tan^2(x-3) | | x^3+8x^2-14x-12=0 | | 5x+10=7x-70 | | c*2+5c+4=0 | | 5y+11=28 | | 6x=178 | | e^11x+5=4 | | -15-4x=7-3 | | 18-3n=3 | | -4n+2=-2n-2 | | 8y-2=7 | | -83=2y-15y-18 | | (3x-4)(2x-9)= | | y=2(x-8)+3 | | 5u+63=8 |

Equations solver categories